Architect competencies according to requirements of the Piura Region - Álvarez Luján, Blanca Lina (2021)
The objective of this study was to establish the specific competences of the architect required by the business market of the Piura region, for which a descriptive, applied, non-experimental, cross-sectional design was carried out; In it, active and existing companies in the construction and real estate sector of the Piura region were considered as the study population and the sample was 219 surveys collected through a two-stage stratified sampling. The results showed that the specific skills of the architect required by the business market of the Piura region coincide with 23 of the 26 identified in the architect's profile for Latin America, likewise, the required knowledge is grouped into 27 thematic lines, the skills of the architect in 19 categories, the attitudes involve six values and six specific attitudes, concluding that the competency approach allows training professionals with an integral vision, but this does not imply that it is static, since considering the development of societies, needs change due to What this study can be applied in each of the regions, where the professional architecture career is offered, since it will allow updating the professional training program, considering the real requirements that society demands in the context where these are directly developed. professionals.